Multi-point aerodynamic design and optimization of a nacelle for an electric fan - Venkatesh, Aravindhan (My University, 2022)
Engines that power commercial airliners are becoming more carbon neutral as propulsion technologies are evolving at a rapid pace, targeting progressive decarbonization goals. Electrification of sub-regional aircraft could be an initial step in controlling emissions in the skies. In accordance with this goal, GKN Aerospace has been leading the EleFanT project that is aimed at developing an electric fan thruster for an electric aircraft. The present multi-point aerodynamic design of the nacelle is done as a part of the Electric Fan thruster (EleFanT) project. A multiobjective shape optimization method was implemented to obtain an initial set of axisymmetric shape parameters for nacelle and nozzle geometries. The optimization workflow consists of a non-dominated sorting genetic algorithm (NSGA-II), coupled with 2-D axisymmetric Reynolds Averaged Navier Stokes (RANS) equations based CFD code. The good designs from 2-D cruise studies were subjected to multi-point analysis, where the 3-D asymmetric flow fields from various operating points like cruise, take-off and crosswind were studied. The aerodynamic drag and thrust coefficients and the engine performance metrics were recorded using a defined bookkeeping method. For the 3-D simulations, a validated faninlet coupling model, the modified parallel compressor (MPC) method was employed at the fan face boundary to adapt to the incoming flow distortions. Thorough investigations on inlet drooping were done to analyze its positive impact on intake aerodynamics. With drooping, besides a reduction in drag coefficient Cd at cruise, mitigation of intake flow separation and distortion at take-off was also achieved. Further, a small increment done to the highlight radius at the lower position of the nacelle gave sizeable reductions in incoming flow distortion at the fan face.
Keywords: aerodynamic design, multi-objective optimization, nacelle design, multi-point analysis, CFD